2017
DOI: 10.5897/ajbm2016.8202
|View full text |Cite
|
Sign up to set email alerts
|

Is gender diversity in ownership structure related to private Italian companies propensity to engage in earnings management practices?

Abstract: The study investigates whether and how gender diversity in ownership structure (here intended as female ownership) is related to private (unlisted) Italian companies' propensity to engage in earnings management practices, specifically in "earnings minimization" (EM) and "earnings change minimization" (ECM). Companies practice EM when they manage earnings to bring them close to zero. They practice ECM, instead, when they manage earnings to avoid large earnings chan ges or, in other words, to "smooth" company ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…With reference to Italian private companies, previous studies have not found that female ownership and the propensity to practice some forms of earnings management are negatively related. Rather, Poli (2017a) has found that the relationship between the incidence of female ownership and the magnitude of abnormal working capital accruals is quadratic, and Poli (2017b) has also found that female-owned and non female-owned companies have the same propensity to engage in "earnings minimisation" and "earnings change minimisation". These results suggest testing the following research hypothesis:…”
Section: The Relationship Between the Gender Of Owners And The Practice Of Shifting Profit From The Fiscal Year In Which The Corporate Stmentioning
confidence: 99%
“…With reference to Italian private companies, previous studies have not found that female ownership and the propensity to practice some forms of earnings management are negatively related. Rather, Poli (2017a) has found that the relationship between the incidence of female ownership and the magnitude of abnormal working capital accruals is quadratic, and Poli (2017b) has also found that female-owned and non female-owned companies have the same propensity to engage in "earnings minimisation" and "earnings change minimisation". These results suggest testing the following research hypothesis:…”
Section: The Relationship Between the Gender Of Owners And The Practice Of Shifting Profit From The Fiscal Year In Which The Corporate Stmentioning
confidence: 99%